2011
DOI: 10.1099/ijs.0.026179-0
|View full text |Cite
|
Sign up to set email alerts
|

Kroppenstedtia eburnea gen. nov., sp. nov., a thermoactinomycete isolated by environmental screening, and emended description of the family Thermoactinomycetaceae Matsuo et al. 2006 emend. Yassin et al. 2009

Abstract: A Gram-positive, spore-forming, aerobic, filamentous bacterium, strain JFMB-ATET, was isolated in 2008 during environmental screening of a plastic surface in grade C in a contract manufacturing organization in southern Germany. The isolate grew at temperatures of 25–50 °C and at pH 5.0–8.5, forming ivory-coloured colonies with sparse white aerial mycelia. Chemotaxonomic and molecular characteristics of the isolate matched those described for members of the family Thermoactinomycetaceae, except that the cell-wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 28 publications
3
28
0
Order By: Relevance
“…The genomic DNA G+C content of strains W9323 T and X0209 T was 45.9 and 50.6 mol%, respectively. These values fall within the range of genomic DNA G+C content reported for the genus Kroppenstedtia as it exists presently (46 to 56 mol%) (von Jan et al 2011, Yang et al 2013.…”
Section: Resultssupporting
confidence: 80%
“…The genomic DNA G+C content of strains W9323 T and X0209 T was 45.9 and 50.6 mol%, respectively. These values fall within the range of genomic DNA G+C content reported for the genus Kroppenstedtia as it exists presently (46 to 56 mol%) (von Jan et al 2011, Yang et al 2013.…”
Section: Resultssupporting
confidence: 80%
“…Members of the Thermoactinomycetaceae are rarely isolated from patient specimens and are difficult to identify by conventional phenotypic testing. Their recognition has been facilitated by molecular identification methods, and several novel species have recently been described (1,2,5,12,14,15). Here we showed that K. eburnea has been repeatedly isolated from clinical specimens in different geographic regions of the United States.…”
mentioning
confidence: 76%
“…These species were not identified in the automated analysis due to short reference sequences or because they had a subspecies annotation not covered in the algorithm. The validity of our approach was confirmed, however, when a novel thermoactinomycete, Kroppenstedtia eburnea ( 32 ), was formally described during preparation of this article. The 16S sequence of this organism showed ≈99.5% identity to a large cluster of 12 isolates in our study (Table 2).…”
Section: Discussionmentioning
confidence: 75%
“…thermoviolaceus . One cluster of 12 isolates belonged to a novel genus and species, Kroppenstedtia eburnea , which was described subsequent to our initial analysis ( 32 ). …”
Section: Resultsmentioning
confidence: 88%